EFFECT OF AUDIT MATERIALITY THRESHOLDS ON AUDIT REPORT IN NIGERIA - Bassey, Bassey Eyo; Bessong, Peter Kekung; Effiong, Charles; Ekperi, Kalada (International Journal of Psychosocial Rehabilitation, 2020)
The role of materiality on audit report nature and quality cannot be overemphasized in the field of auditing. Yet a general consensus on the applicable threshold has been elusive to practitioners and researchers. With this in mind this paper seeks to empirically investigate the effect of audit materiality on audit reports in Nigeria. Three auditing firms were chosen and annual financial data for their clients in the banking industry were collected. The Panel OLS and Granger Causality tests were used to test for materiality threshold effects and variations on audit reports. Three benchmarks were used to calculate audit report quality namely accurateness, two hypotheses were constructed and tested at 0.05 percent level of significance. Both results from the empirical tests shows that materiality thresholds significantly affect audit report in the country. The study concluded that since materiality thresholds are important in influencing the nature of audit report, audit firms should do more to study the financial information of their clients that brought about their conclusions on thresholds used.